Implementing fencing as adapted physical activity in non-metastatic breast cancer patients: design and early rehabilitation strategy of the FENICE study protocol - Berretta, Massimiliano; Garozzo, Daniele; Foti, Calogero; Roselli, Mario; Materazzo, Marco; Vita, Giulia; Iellamo, Ferdinando; Scordari, Marco; Di Mauro, Giordana; Spatari, Giovanna; Ottaiano, Alessandro; Noce, Annalisa; et al. (Frontiers in Oncology, 2024)
Background: Improving prognosis of BC patients has drawn the attention of health care professionals on disease related long-term side effects and on the multiple treatments BC patients must undergo. Despite advances in procedures, surgery still has multiple detrimental effects, including pain, edema, and limited mobility. For this reason, fostering adapted physical activity (APA) and healthy lifestyle (including a balanced diet and weight management) should become an everyday purpose of healthcare professionals. Fencing may be a well-suited activity to counteract fatigue, pain, and limited arm mobility. Method and analysis: the FENICE study is a mono-center, randomized clinical trial targeting women with BC stages I-III within four weeks from BC surgery. Participants in the control arm will receive the usual recommendations based on the good clinical practice guidelines. In the study arm, participants will be treated with the usual clinical and therapeutic recommendations together with APA and correct lifestyle suggestions.The primary objective of the study is to compare whether implementation of APA and healthy lifestyle in BC patient after surgery will result in an overall improvement of physical and mental status.Fencing and its early application in postoperative period may represent a feasible strategy to be implemented in the rehabilitation journey of BC patients.The study protocol FENICE has been approved by an Italian Ethics Committee on May 2023 (R.S 100.23 5 th May 2023).